URGENSI UNDANG-UNDANG NOMOR 20 TAHUN 2008 BAGI PENGEMBANGAN UMKM SEKTOR KULINER DALAM RANGKA MENDORONG KULINER BERSERTIFIKASI HALAL - Andi Fariana; Wahidatur Rosyidah (Komunitas Manajemen Kompetitif, 2026)
In the period of 2023-2024, MSMEs in Indonesia were recorded as contributing 61% of GDP (Rp. 9,580 trillion) and absorbing more than 123 million (97% of the workforce), while the number of culinary MSMEs in Bekasi Regency was 15,156, which absorbed 410,000 workers in 2023. MSMEs in the culinary sector are included in the types of micro, small, and medium enterprises as referred to in the Law of the Republic of Indonesia Number 20 of 2008. This study uses a descriptive qualitative research method through data collection through interviews and observations. A search was conducted on related laws and regulations (statute approach) to find out the fact that Law Number 20 of 2008 concerning the development of MSMEs is an important thing that should be a guideline in terms of issuing various policies, handling, and coaching for MSMEs in the culinary sector in Bekasi Regency in order to encourage halal-certified culinary. The halal certification policy provides convenience for consumers and makes MSMEs resilient and independent as stipulated in Article 5 of Law Number 20 of 2008. The results of this study indicate that MSMEs in the culinary sector in Bekasi Regency continue to increase, but awareness or belief in the importance of halal certification is not as it should be, so the Regional Government together with BPJPH and MUI needs to continue to encourage MSME awareness of the importance of halal certification and provide convenience to MSMEs to obtain free halal certification.